Effect of Radiation on Employers in Radiology (X- rays, CT Scan and Magnetic Resonance Imaging )In Al-muthanna Province-Iraq - Hanaa Ali Aziz (Journal of Global Pharma Technology, 2018)
The aim of this study was evaluated the effect of radiation on the hematological parameter of employers in X- rays, CT scan and MRI units, during the period from October-2016 up to March–2017. Fifty sample were examined in the present study as well as twenty apparently healthy people selected as the control, their ages ranged between 25-36 years old. The samples were examined by using hematological tests. The study showed a significant increase at (P<0.05) in Male, age groups (31-36) and blood group B. The study indicated a significant decrease at (P<0.05) in red blood cells(RBC) and hemoglobin (HB) compared with control groups. Also, indicated a significant increase at (P<0.05) in white blood cells (WBC), Neutrophil, Monocyte and Lymphocyte compared with control groups. Keywords: Hematological, Radiation, MRI, CT scan, Iraq.